ANALISIS PENGARUH NILAI TUKAR, SUKU BUNGA, LAJU INFLASI, PERTUMBUHAN GDP DAN INDEKS DOW JONES TERHADAP INDEKS HARGA SAHAM SEKTOR PROPERTI (Kajian Empiris Pada Bursa Efek Indonesia Periode Tahun 2001-2010 ) - , Andy Dediyono ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The property sector as one of the important sectors in Indonesia. Development of this sectors has corelation with macro economic conditions. Growing businesses in the property sector will also affect the property stock price index in Indonesia stock market. The purpose of this reseach is to analyze the influence of macro economic indicators, inflation rates, interest rates, currency rate, Dow Jones index and GDP (Gross Domestic Product) growth in the property stock price index during period 2001-2010. This recseach use secondary data, they are Monthly data of Property Stock Price Index (IHSP), Interest rate (SBI), Currency rate, Inflation rate, GDP Growth and Dow Jones Index from January 2001 to December 2010 (120 observations). The model used in this reseach is multiple regression analysis with least squares (OLS = Ordinary Least Square) method. The results shows that the currency rate,interest rates(SBI), Inflation rate, GDP growth and the Dow Jones index affect the property stock price index. Partially, the GDP growth and the Dow Jones index have positive effect and significant. Inflation rate has positive effect but it is not a significant. Currency rate has negative effect and significant. SBI rate has negative effect and it is not significant. In this reseach the dependent variable can be explained by the independent variable by 28 percent and 72 percent are explained by other factors outside of this reseach.